Effect of A Neuropsychological Intervention Program On The Development of Academic Skills in The First Years of School - Ayala Arango, Astrid Yamile (2023)
A quasi-experimental study was carried out with the objective of determining the effect of a neuropsychological intervention program on academic skills in reading, writing and mathematics in a group of first grade girls and boys of primary school at the Cadena Las Playas educational institution. municipality of Apartadó, Antioquia, Colombia, aged between 5 and 6 years, belonging to a low socioeconomic condition. Two groups were formed, the experimental and the control, each with 19 students. Measurement tests in reading, writing and arithmetic were applied to each participant. Subsequently, a neuropsychological intervention program was applied to the experimental group for seven months, consisting of group training using the NeuronUP kids program. At the end, measurements were applied again in the academic skills of both groups.   At the pretest level, no significant differences were found between the groups except for the word and non-word writing subtest in favor of the experimental group. The post-test assessment showed significant differences that indicate that the experimental group had a better performance in reading syllables, words, non-words, sentences, words with reading errors aloud and speed of reading aloud and in writing syllables. (p>0.05), in arithmetic no significant differences were found. In conclusion, the use of a neuropsychological stimulation program contributed favorably to the development of academic skills such as reading and writing, representing an opportunity to implement in the school setting and specifically in the classroom, neuropsychological-based programs that meet an objective. preventive that favors learning processes in the school population who are in less enriched environments.